A qualitative insight into the relationship between postpartum depression and body image. (27th May 2021) - Hartley, Eliza; Fuller-Tyszkiewicz, Matthew; Skouteris, Helen; Hill, Briony
ABSTRACT: Objective : This study qualitatively explored the experience of depression and body image concerns in women diagnosed with depression in the postpartum period. Background : Women's bodies undergo substantial changes during the perinatal period which can impact their body image and mood post-birth.However, it remains unknown how women diagnosed with depression experience their body image in the postpartum period. Methods : Seventeen women in their firstpostpartumyear completed qualitative telephone interviews: seven women diagnosed with depression and ten without depression. Thematic content analysis identified the main themes of the women's narratives: 1) expectations and adjustments to motherhood; 2) mood in response to changing postpartum body; 3) the context of feeling bad about my body; and 4) body letting me down and relationship to mood. Results : Differences in the relationship between body image and mood for postpartum women with depression compared to women without depression were revealed. Other themes seemed to be experienced in the same way by women with and without depression. Conclusion : Poor body image and depressive symptoms appear linked during postpartum. An improved understanding of this association may assist postpartum women to manage negative body image post-birthand prevent the exacerbation of negative emotional health in this period.